Profil Usaha Industri Garmen “Vandev” di Kota Malang (Studi Usaha Industri Garmen “Vandev” di Kota Malang) - Riska Marianti; Nur Endah Purwaningsih; Idah Hadijah (Universitas Ngeri Malang, 2021)
Managing a business such as a garment must have clear organizational structure, financial management, and production implementation so that company goals can be achieved according to the targets set by a company. The purpose of this research is to describe the business studies in